Highly sensitive naked eye detection of Iron (III) and H2O2 using poly-(tannic acid) (PTA) coated Au nanocomposite - Fang, Yan (2019)
In the present study, we present a room temperature-, one-pot method for the synthesis of functional poly (tannic acid) (PTA)-based core@shell nanocomposites (core@PTA). The addition of tannic acid (TA) to gold (Au) salt solutions at mildly alkaline pH induced reduction of the metal salts to Au nanoparticles (NPs) while TA was oxidized and self-polymerized before encapsulating the AuNPs to form Au@PTA. Through the use of coordination chemistry, the synthesized Au@PTA was utilized as a naked eye sensor for iron (III) ions and H2O2. In the presence of Fe3+, Au@PTA aggregated and resulted in visible color change, showing high selectivity towards Fe3+ with visual detection limit of 20 μM. Extension of the approach is used to detect H2O2 with visual detection limit of 0.4 μM. Observation of the UV–vis spectra after the addition of analytes for the two detection systems revealed an additional peak in the H2O2 detection system at ∼ 650 nm. This is due to the presence of “wire-like” oligomer structures in the H2O2 detection system as opposed to nanocomposite aggregation observed in the former system.